The Ethics of Pain Management in the Pediatric Population - Pinto-Coelho, Adelaide; Trindade, Hugo (Journal of the Portuguese Society of Anesthesiology, 2018)
The prescription of off label analgesic medications in pediatric age is a constant reality in modern healthcare. Off label prescription happens when a drug is used beyond the product licensing according to its indications, age group, weight, frequency, presentation or route of administration. Due to ethical issues, clinical trials in pediatric population are controversial. Consequently many drugs used in Pediatrics are not sufficiently tested for efficiency and safety. An ethical dilemma arises, for it is the doctor’s duty to effectively treat children’s pain, even if that means off label prescription of analgesics. In this review paper we address the issue of off label drug use for pain control in the pediatric population.